The effects of shortening potential benefit duration: Evidence from regional cut-offs and a policy reform - Ewa Gałecka-Burdziak; Marek Góra; Jonas Jessen; Robin Jessen; Jochen Kluve (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
We quantify labour market effects of changes in the potential benefit duration (PBD) in Poland. Individual workers' PBD depends on the county unemployment rate relative to the national average - 12 months of PBD above a cut-off of 125 per cent and 6 months below. This cut-off shifted from 125 to 150 per cent in a 2009 reform. We utilize i) the natural experiment of the reform and ii) the sharp discontinuity generated by the cut-offs to estimate effects of shortening the PBD. Our administrative data cover unemployment spells for prime age workers during the years 2006-2018. A one-month shorter PBD decreases average benefit duration by 0.5 months and average unemployment duration by 0.4 months. The PBD reduction by six months increased the job finding rate within the first 9 months by 6 percentage points. Using the stock of unemployed per county, we find evidence for positive aggregate employment effects. – – Wir quantifizieren Arbeitsmarkteffekte von Veränderungen der maximalen Bezugsdauer des Arbeitslosengelds in Polen. Die maximale Bezugsdauer eines Arbeitslosen hängt von der Arbeitslosenquote des Landkreises relativ zum nationalen Durchschnitt ab. Sie betrug 12 Monate über einem Schwellenwert von 125 Prozent und 6 Monate darunter. Im Zuge einer Reform im Jahr 2009 wurde dieser Schwellenwert von 125 auf 150 Prozent erhöht. Wir verwenden i) das natürliche Experiment der Reform und ii) die Diskontinuität am Schwellenwert, um Effekte der Kürzung der maximalen Bezugsdauer zu schätzen. Wir verwenden administrative Daten über Arbeitslosigkeitsspells in den Jahren 2006-2018. Eine Kürzung der maximalen Bezugsdauer des Arbeitslosengelds um einen Monat verkürzt die durchschnittliche Dauer des Arbeitslosengeldbezugs um 0,5 Monate und die der Arbeitslosigkeit um 0,4 Monate. Die Verkürzung der maximalen Bezugsdauer um 6 Monate erhöhte die Übergangsrate in Beschäftigung innerhalb der ersten 9 Monate der Arbeitslosigkeit um 6 Prozentpunkte. Zudem betrachten wir den Bestand an Arbeitslosen pro Kreis und finden Evidenz für positive aggregierte Beschäftigungseffekte der Reform.
Keywords: H55; J20; J65; 330; Unemployment benefits; extended benefits; spell duration